Analysis of a maritime transport chain with information asymmetry and disruption risk. (1st January 2023) - Zhao, Nenggui; Wang, Zhipeng; Ji, Xiang; Fu, Hong; Wang, Qiang
Abstract: Maritime transport chain is facing huge information asymmetry after the outbreak of major emergencies, such as COVID-19 epidemic. The previous literature has proved that information investing and information sharing are two effective tactics to relieve information asymmetry between supply chain nodes, and help them improve the performance of the supply chain. This paper assumes random demand disruption is the main cause of the information asymmetry in a maritime transportation chain. To explore how the random demand disruption and channel competition jointly impact operational decisions in a dual-channel maritime transport chain composed of one port, two carriers and shippers, we construct a game-theoretical basic model, and proposed two strategies, i.e., information investing and information sharing. Several significant managerial insights are derived. First, we find that inaccurate disruption information leads to inaccurate decisions and huge losses; Second, investing in precise information benefits the port only if the chain members are optimistic about the market, and improves the revenue of the carrier who invested in information if the investment cost is reasonable; Third, accepting information sharing benefits the port only when the precise disruption and the distortion of information are relatively large, as well as the misappropriate rate is relatively small; and only when the port is pessimistic about the market or the channel competition is weak, sharing information may hurt the carrier who invested in information. Finally, the strength of the channel competition will enhance the impact of information inaccuracy on the maritime transport chain. Highlights: A maritime transport chain with information asymmetry and disruption risk is studied. Two managerial strategies for improving the performance are analyzed. The information investing strategy is not always beneficial for the port. The information sharing strategy hurts the carrier when channel competition is weak.